Colorimetric Method for Detecting Amplified Nucleic Acids. (October 1998) - Durward, Elaine; Harris, William J.
Methods for detecting and measuring, the success of nucleic acid sequence amplifications, can be developed by detecting the by-products of amplification procedures. One method includes the detection of inorganic phosphate (Pi) during or on completion of the PCR. The method requires modification of assay conditions to prevent thermal- and template-independent enzymatic activity from nonspecifically hydrolyzing dNTPs. Detection of Pi by the traditional Fiske-SubbaRow method provides a sensitivity similar to ethidium bromide staining of amplified products. The method offers a simple and rapid assay for amplified nucleic acids and can be useful in assays where confirmation of the amplified DNA product is not essential.